63=4y-13t

Simple and best practice solution for 63=4y-13t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 63=4y-13t equation:


Simplifying
63 = 4y + -13t

Reorder the terms:
63 = -13t + 4y

Solving
63 = -13t + 4y

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '13t' to each side of the equation.
63 + 13t = -13t + 13t + 4y

Combine like terms: -13t + 13t = 0
63 + 13t = 0 + 4y
63 + 13t = 4y

Add '-63' to each side of the equation.
63 + -63 + 13t = -63 + 4y

Combine like terms: 63 + -63 = 0
0 + 13t = -63 + 4y
13t = -63 + 4y

Divide each side by '13'.
t = -4.846153846 + 0.3076923077y

Simplifying
t = -4.846153846 + 0.3076923077y

See similar equations:

| x+8=-19 | | 5(x+3)=3(2x+1) | | y-27=4y | | 5n+45=50 | | 18(x+2)=4x+34 | | 5y+2=11 | | 4x-20+7=35 | | 6x+5=0 | | 6+5y=0 | | 18-r=6 | | 6c=-36 | | 2(4x-1)=2 | | 13=-64 | | 4p=24 | | 15=3x-3 | | -2x+13=3x-3 | | 13=-7y | | 4b+6b=2 | | 2r=10 | | -(.66)(-9y)(1.5)(8x)(1)= | | 7x+29=2x+109 | | 12x+23=5x+135 | | -18+2=7w+5w | | 216-6x=39x+21 | | 169-7x=38x+19 | | 9-8x=27-22x | | -52-7x=10x+16 | | 5x+9=-99-7x | | 75-2x=4x+9 | | -16-5x=14-10x | | 70-2x=10x+22 | | 3x+11=53-3x |

Equations solver categories